The plight of civic parties in divided societies - Murtagh, Cera (International Political Science Review)
Civic political parties in divided societies occupy an ambiguous place in the power-sharing literature. Scholarship tends to focus on ethnic parties and assumes civic actors to be marginal. The empirical reality tells a different story: civic parties have contributed to peace, stability and democracy in some of the world$1 (Bs most deeply divided places by playing a mediating role, acting as a moderating force and representing otherwise marginalised groups. Drawing from interviews with representatives from civic parties, ethnic parties and civil society in Northern Ireland and Bosnia and Herzegovina, and broader institutional analysis, I argue that civic parties$1 (Bsurvival can be explained by the fact that they meet therein not only with barriers but also critical openings. They adapt to this opportunity structure, with different party types developing under different forms of power-sharing. In illustrating the relationship between governance models and civic parties, this article underlines the importance of post-settlement institutional design.- Reproduced s
Keywords: Civic political parties, Power-sharing, Divided societies, Northern Ireland, Bosnia and Herzegovina, Post-settlement institutional design